Odstępstwa od normy w kategorii gramatycznej liczby w powieści Wojna polsko-ruska pod flagą biało-czerwoną i ich odzwierciedlenie w przekładzie na język rosyjski - Orzechowska, Joanna (Studia Rossica Posnaniensia, 2020)
Dorota Masłowska’s Wojna polsko-ruska pod flagą biało-czerwoną employs various types of linguistic innovations. One of them is a mistaken selection of the number of nouns. This stylistic means results in linguistic humour. In the Russian translation of the novel reflecting this phenomenon should not pose any problems. However, neither of the instances of the stylistic means analysed in the paper was reflected in the Russian target text. It is difficult to determine why the translator did not attempt to show Russian readers a reconstruction of the language of the Polish text. As a result, Irina Lappo’s translation lacks the poetic qualities and refreshing touches of Masłowska’s language.